The impact of social franchising on the use of reproductive health and family planning services at public commune health stations in Vietnam - Pham Van; Alden Dana L; Ngo Anh D; Phan Ha (BMC, 2010)
Abstract Background Service franchising is a business model that involves building a network of outlets (franchisees) that are locally owned, but act in coordinated manner with the guidance of a central headquarters (franchisor). The franchisor maintains quality standards, provides managerial training, conducts centralized purchasing and promotes a common brand. Research indicates that franchising private reproductive health and family planning (RHFP) services in developing countries improves quality and utilization. However, there is very little evidence that franchising improves RHFP services delivered through community-based public health clinics. This study evaluates behavioral outcomes associated with a new approach - the Government Social Franchise (GSF) model - developed to improve RHFP service quality and capacity in Vietnam's commune health stations (CHSs). Methods The project involved networking and branding 36 commune health station (CHS) clinics in two central provinces of Da Nang and Khanh Hoa, Vietnam. A quasi-experimental design with 36 control CHSs assessed GSF model effects on client use as measured by: 1) clinic-reported client volume; 2) the proportion of self-reported RHFP service users at participating CHS clinics over the total sample of respondents; and 3) self-reported RHFP service use frequency. Monthly clinic records were analyzed. In addition, household surveys of 1,181 CHS users and potential users were conducted prior to launch and then 6 and 12 months after implementing the GSF network. Regression analyses controlled for baseline differences between intervention and control groups. Results CHS franchise membership was significantly associated with a 40% plus increase in clinic-reported client volumes for both reproductive and general health services. A 45% increase in clinic-reported family planning service clients related to GSF membership was marginally significant (p = 0.05). Self-reported frequency of RHFP service use increased by 20% from the baseline survey to the 12 month post-launch survey (p < 0.05). However, changes in self-reported usage rate were not significantly associated with franchise membership (p = 0.15). Conclusions This study provides preliminary evidence regarding the ability of the Government Social Franchise model to increase use of reproductive health and family planning service in smaller public sector clinics. Further investigations, including assessment of health outcomes associated with increased use of GSF services and cost-effectiveness of the model, are required to better delineate the effectiveness and limitations of franchising RHFP services in the public health system in Vietnam and other developing countries.